Ma’ad: Upaya Bermuamalah Di Era Revolusi Industri 4.0 - Najih, Rifqi Abqory; Hamhij, Durroh Nihayah (JURNAL JAWI, 2020)
The The presence of the Industrial Revolution 4.0 is a hope for every market player to exist and develop, because the progress of a business does not always depend on the level of capital owned but is determined by strategy, innovation and digitization. Data and facts prove that those who take the initiative for change and are careful in combining innovation and technology have emerged as the new rulers in the global industrial area. But on the other hand the Industrial Revolution 4.0 can also erode labor absorption and stop the existence of most of the colonial generation who are blind to technology. This research aims to provide the guidance for the society for preparing muamalat in the Industrial Revolution 4.0. The method of this research was descriptive qualitative which emphasized of the meaning, natural description, and plot. The result of this research indicate that industrial revolution can be overcome when people are able to position themselves and take existing the opportunities through the implementation of Ma’ad concept as taught in Islam. This research concludes that Ma’ad concept is the answer to faceing the industrial revolution without being rolled and rolled by technological developments.